From IT to Tablet: Current Use and Future Needs in Kindergartens - Nina Bølgan (Universitetsforlaget, 2012)
This article describes chronologically the main lines of the implementation of ICT in kindergartens, and ICT's place in education programmes from the mid-1990s until today. It discusses the lack of interest among public authorities in recognizing the role technology can have in modern early childhood and the necessity of promoting digital literacy in kindergartens and pre-school teacher education.